The Relationship Between The Electromyographic Activity Of Rectus And Oblique Abdominal Muscles And Bioimpedance Body Composition Analysis - A Pilot Observational Study - Ptaszkowski K (Dove Medical Press, 2019)
Kuba Ptaszkowski, Paulina Wlodarczyk, Malgorzata Paprocka-Borowicz Department of Clinical Biomechanics and Physiotherapy in Motor System Disorders, Wroclaw Medical University, Wroclaw 51-355, PolandCorrespondence: Kuba PtaszkowskiDepartment of Clinical Biomechanics and Physiotherapy in Motor System Disorders, Wroclaw Medical University, Wybrzeże L. Pasteura 1, Wroclaw 51-355, PolandTel +487117840183Fax +48717840182Email kuba.ptaszkowski@umed.wroc.plPurpose: Measurements using surface electromyography (sEMG) may be more complicated when the different thickness of the subcutaneous tissue layer is observed, therefore it is important to show the influence of fat tissue on the results of sEMG measurements. The main aim of the study was to assess the relationship between the sEMG RMS value of rectus and external oblique muscles of the abdomen and the composition of the body, which was assessed using bioelectrical impedance analysis.Patients and methods: The target group was made up of healthy people aged 20-30-year-old. The study visit protocol of the participants was as follows: a medical history, instructions on the purpose of measurements and examination procedures, obtaining consent for participation in the research, an analysis of the body weight composition by the electrical bioimpedance method, a fat tissue thickness measurement using body fat calipers, preparation of the subject for sEMG measurements (sEMG RMS value of rectus and external oblique abdominal muscles).Results: Twenty-nine people were qualified for the study according to the inclusion and exclusion criteria. sEMG amplitudes decreased when the person had a higher fat content and had less water in the body. These results were related to the rectus abdominal muscle (mainly its upper part) during the active contraction of this muscle. In addition, it was observed that when actively bent their torsos forward people with a higher BMI and with a greater thickness of fat tissue had a lower sEMG RMS value of the rectus abdominal muscle.Conclusion: In order to conduct reliable examinations using sEMG, parameters concerning the amount of fat tissue, the thickness of fat tissue, BMI and amount of water in the body should be taken into account.Keywords: surface electromyography, body mass index, bioelectrical impedance, abdominal fat, skinfold thickness